A primer to planetary health in evidence-based medicine and clinical decision-making - Ebm, Claudia; Herrmann, Alina; Bognanni, Antonio; Aloosh, Mehdi; Michels, Charlotte; Vieira, Rafael; Leontiadis, Grigorios; Piggott, Thomas; Schuenemann, Holger J. (BMJ evidence-based medicine, 2025)
The healthcare sector is experiencing profound change, shaped by demographic shifts, technological innovation and, increasingly, environmental pressure.1 Climate change, biodiversity loss and ecosystem degradation are widely recognised as critical determinants of human health, influencing disease patterns, exacerbating health inequalities and threatening the operational resilience of healthcare delivery.2 - - In this evolving context, clinicians are increasingly expected to deliver high-quality, evidence-based care while also considering the broader ecological and societal factors that influence health outcomes.3 4 Planetary health, a transdisciplinary field concerned with the interconnections between human health and the health of natural and social systems, offers a critical framework for navigating this complexity.5 At its core, planetary health seeks to promote human health and well-being within the limits of the Earth’s ecological capacity, known as planetary boundaries. These boundaries define the safe operating space for humanity in relation to nine critical Earth system processes, including climate change, biodiversity loss and various forms of pollution.6 - - Understanding and respecting these boundaries is not just a matter of environmental stewardship; it has direct implications for healthcare practice. Health systems are increasingly affected by ecological disruptions such as heatwaves, vector-borne diseases and resource scarcity.7 At the same time, they are major contributors to environmental harm. For instance, the sector is responsible for approximately 4%-5% of global greenhouse gas emissions, with clinical decisions such as prescribing, diagnostics and procurement significantly contributing to this footprint.8 Clinicians are well positioned to respond to these challenges. Beyond treating the health consequences of the transgression of planetary boundaries, they can influence institutional practices and advocate for systemic reform.6 Yet, despite this potential, planetary health remains largely absent from routine clinical reasoning. This disconnect is shaped by structural barriers, limited training and the inherent difficulty of balancing planetary health with immediate patient care. …
Vorab online veröffentlicht: 20. November 2025
Gesehen am 29.01.2026